Music, Empathy, and Affiliation: Commentary on Greenberg, Rentfrow, and Baron-Cohen - Vuoskoski, Jonna K (Empirical Musicology Review, 2015)
Empathy and social cognition arguably play a crucial role in our engagement with music. In response to the account offered by Greenberg, Rentfrow, and Baron-Cohen, this commentary considers an alternative—yet complementary—explanation for how music making and music listening might be able to evoke empathy and affiliation. This alternative explanation stems from the perception–action model of empathy, and the affiliation-evoking effects of mimicking and synchronized actions. In light of this alternative account, I will also explore the potential contribution of dispositional empathy to music preferences and music perception as suggested by Greenberg and colleagues.